Synthetic analogues of marine bisindole alkaloids as potent selective inhibitors of MRSA pyruvate kinase - Veale, Clinton Gareth Lancaster (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
Globally, methicillin resistant Staphylococcus aureus (MRSA) has become increasingly difficult to manage in the clinic and new antibiotics are required. The structure activity relationship (SAR) study presented in this thesis forms part of an international collaborative effort to identify potent and selective inhibitors of an MRSA pyruvate kinase (PK) enzyme target. In earlier work the known marine natural product bromodeoxytopsentin (1.6), isolated from a South African marine sponge Topsentia pachastrelloides, exhibited selective and significant inhibition of MRSA PK (ICâ‚…â‚€ 60 nM). Accordingly bromodeoxytopsentin provided the initial chemical scaffold around which our SAR study was developed. Following a comprehensive introduction, providing the necessary background to the research described in subsequent Chapters, this thesis has been divided into three major parts. Part one (Chapter 2) documents the synthesis of two natural imidazole containing topsentin analogues 1.40, 1.46, five new synthetic analogues 1.58"”1.61, 2.104. In the process we developed a new method for the synthesis of topsentin derivatives via selenium dioxide mediated oxidation of N-Boc protected 3-acetylindoles to yield glyoxal intermediates which were subsequently cyclized and deprotected to yield the desired products. Interestingly we were able to demonstrate a delicate relationship between the relative equivalents of selenium dioxide and water used during the oxidation step, careful manipulation of which was required to prevent the uncontrolled formation of side products. Synthetic compounds 1.40, 1.46, 1.58"”1.61 were found to be potent inhibitors of MRSA PK (ICâ‚…â‚€ 238, 2.1, 23, 1.4, 6.3 and 3.2 nM respectively) with 1000-10000 fold selectivity for MRSA PK over four human orthologs. In the second part of this
Keywords: Alkaloids; Pyruvate kinase; Staphylococcus aureus; Antibiotics; Sponges -- South Africa; Imidazoles; Biological assay; Antibacterial agents